Front Cover. Issue 6 (21st May 2019) - Thorne, Lesley H.; Baird, Robin W.; Webster, Daniel L.; Stepanuk, Julia E.; Read, Andrew J.
Abstract : The cover image is based on the Biodiversity Research Predicting fisheries bycatch: A case study and field test for pilot whales in a pelagic longline fishery by Lesley H. Thorne et al., DOI: 10.1111/ddi.12912 . Image Credit: Will Cioffi, Duke University Marine Lab.